Pengaruh Work to Family Conflict dan Family to Work Conflict Terhadap Performa Kinerja Diantara Para Perawat dengan Dukungan Sosial Sebagai Variabel Moderasi (Studi pada Rumah Sakit Panti Waluyo Surakarta) (STIE St. Pignatelli Surakarta, 2019)
This research aimed to analyze the influence of work to family conflict and work to family conflict on job performance for nurses with social support as moderation variable. This research was done to 76 nurses of outpatient in Hospital of Panti Waluyo Surakarta. The participants were those who have worked for one year and got married. The regression analysis found that work to family conflict and family to work conflict had negative and significant influence on nurses job performance, while social support had positif and significant influence on nurses job performance. The hierarchical regression analysis indicated that social support is able to moderate work to family conflict and family to work conflict on nurses job performance.